Handbook of modern sensors : physics, designs, and applications. - Fraden, Jacob, ....- (New York : Springer, 2004)
1 Data Acquisition 2 Sensor Characteristics 3 Physical Principles of Sensing 4 Optical Components of Sensors 5 Interface Electronic Circuits 6 Occupancy and Motion Detectors 7 Position, Displacement, and Level 8 Velocity and Acceleration 9 Force, Strain, and Tactile Sensors 10 Pressure Sensors 11 Flow Sensors 12 Acoustic Sensors 13 Humidity and Moisture Sensors 14 Light Detectors 15 Radiation Detectors 16 Temperature Sensors 17 Chemical Sensors 18 Sensor Materials and Technologies
Keywords: Sensoren